PENERAPAN TEKNOLOGI DAN DIGITAL MARKETING PADA UMKM BRIKETKU ARANG BATOK KELAPA GUNA PENINGKATAN PRODUKTIVITAS USAHA - Riswan Eko Wahyu Susanto; Agus Dani; Yohan Bahtiar; Miftakhul Huda; Setiyo Rojikin; Ahsin Fahmi Mubarok (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Based on data from the East Java Central Statistics Agency (BPS), coconut production in East Java province in 2022 was recorded at 231,934 tonnes. This data shows that East Java is one of the coconut production centres in Indonesia, which reached a national production of 2.87 million tonnes in the same year. However, the obstacles often faced by MSMEs are the limitations of the equipment and technology used in printing, drying and marketing briquettes. Most of the equipment and technology available today is still manual and unable to optimally meet production needs. One such MSME is Briket ‘Batu Bara’, located in Babadan Hamlet, Ngebrak Village, Gampengrejo Sub-district, Kediri Regency. With the available TTG briquette moulding machines and drying ovens, it is hoped that the production process can be accelerated and production output increased. The method used is the provision of tools/machines as well as assistance in the use of machines and digital marketing training for partners.The tangible results of this community service activity include an increase in productivity. Previously, manual production involved two stages, with the printing process followed by oven drying, taking 120 minutes per kilogram and yielding 40 kilograms of product per day. Now, the process takes 10 minutes less per kilogram, while product yield has increased to 40 kilograms per day. The predicted average profit increase is approximately 39.21%, while the average increase in rupiah is 1.034 million rupiah. Thus, the data for July 2025 and September 2025 shows a significant increase of 46.87%. This increase is attributed to the optimal utilisation of the machine developed through the PKM project, coupled with enhanced marketing efforts using digital marketing platforms such as ‘Shopee’.